2016
DOI: 10.1016/j.ijrobp.2015.12.371
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Confers Radioprotection in Murine Salivary Glands

Abstract: Purpose Xerostomia is a common radiation sequela, which has a negative impact on the quality of life of patients with head and neck cancer. Current treatment strategies offer only partial relief. Botulinum toxins (BTX) have been successfully used in treating a variety of radiation sequelae such as cystitis, proctitis, fibrosis, and facial pain. The purpose of this study was to evaluate the effect of BTX on radiation-induced salivary gland damage. Methods and Materials We used a previously established model f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…4). In accordance with previous studies, radiation treatment significantly decreased salivation in saline-treated mice (13, 2426). In this study, the lowest doses of MnBuOE (0.6/0.3 or 0.2/0.1 mg/kg) gave the highest level of protection against xerostomia.…”
Section: Resultssupporting
confidence: 92%
“…4). In accordance with previous studies, radiation treatment significantly decreased salivation in saline-treated mice (13, 2426). In this study, the lowest doses of MnBuOE (0.6/0.3 or 0.2/0.1 mg/kg) gave the highest level of protection against xerostomia.…”
Section: Resultssupporting
confidence: 92%
“…The potential mechanism involved might be related to the reduction in inflammatory infiltration, which has been reported in various organs, including the liver, intestine, and heart [4–6,10]. In addition, Zeidan et al [33] only observed a significant increase at the level of myeloperoxidase on the 3rd day after irradiation in mouse submandibular glands. Zhang et al [34] also observed that only the myeloperoxidase activity peaked on the 3rd day after radiation damage to the intestinal epithelial cells and decreased to nearly normal levels on the 7th day.…”
Section: Discussionmentioning
confidence: 99%
“…A review of natural and synthetic compounds suggested that more studies were needed, and at the time, it was better to use natural compounds over synthetic 13,40‐43 . Botulinum toxin seems to confer radioprotective properties to salivary glands in Murine subjects by reducing glandular atrophy and periductal fibrosis during classic external radiation 44 . Botulinum toxin would be an interesting preventive treatment for patients receiving radioiodine to prevent adverse side effects.…”
Section: Discussionmentioning
confidence: 99%